Study on the application of wavelet threshold denoising in the detection of coal spectra by LIBS. Issue 1 (1st December 2022) - Wang, Shouya; Meng, Deshuo; Zhang, Ke
Abstract: Laser-induced breakdown spectroscopy (LIBS) is a fast spectral detection technology, which has been widely used in coal composition detection and soil pollution detection in recent years. In the process of detection, due to various reasons, the spectrum obtained is mixed with noise, which has a negative impact on the accuracy of subsequent analysis. In this paper, taking the detection of coal by LIBS spectrum as an example, wavelet threshold denoising is used to denoise the detection spectrum containing noise. Different threshold methods are used to compare the denoising effects through simulation, so as to make full preparations for further accurate analysis of the spectrum.